High water level observations along the upper course of the Olt River (Romania) from a hydrological modelling aspect - Szopos , Noémi Mária; Czellecz, Boglárka (Acta Geographica Debrecina Landscape & Environment series, 2017)
Along its upper course, the Olt River (Romania) flows through several settlements, which are endangered by flooding. The multiannual water flow at Tomești station, the first hydrometric station along the Olt River, is 1.51 m3 /s, but in case of extreme events the river flow reached even 41.8 m3 /s. The aim of this study is to analyze the flood events along the upper course of the Olt River (section between Tomești and Cârța settlements) by using the HEC-RAS and the HEC-GeoRAS hydrological modeling software programs. The river cross section model showed how the main channel narrowed (characteristic to some locations) which can be considered as one of the causes of a possible overflow.